Sistem jaringan governans untuk Langkawi Geopark: pengkisahan konseptual - Chan , Kim Ling@Geraldine; Sarah Aziz,; Halimaton Saadiah Hashim,; Rahimah Abdul Aziz., (Universiti Kebangsaan Malaysia, 2010)
In June 2007, Langkawi was accorded a ‘geopark’ status by UNESCO Global Geopark Networks. This status recognises that Langkawi has valuable natural resources such as geological, ecological, cultural and archaeological, that are of high heritage and conservation value, and which could contribute to sustainable economic development through geo-tourism. Since 2007, the management of Langkawi as a geopark involves elements such as work relationships, management structure, functions, “actors” (government and non-government agencies) and various activities for geopark development. These elements are similar to elements found in the governance of any organisation, area or project, geared towards sustainable development and heritage conservation. This article proposes that the management and administration of Langkawi would be better conceptualised and understood as ‘governance,’ namely governance network system. This article also briefly sets out the governance network elements that can strengthen the existing governance system based on the geopark concept. It also aims to provide a holistic conceptual and theoretical understanding of the current governance network system, and concepts related to governance effectiveness. The understanding is developed from a combination of some findings from an on-going research on the governance system of Langkawi Geopark, some conventional and basic governance ideas and sociological ideas about social networks. Through such understanding, this article hopes to identify existing governance problems and put forward proposals to resolve key issues and strengthen existing systems that will enable Langkawi to be governed more efficiently and effectively as a geopark.